Answer:
y =
![(10)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5s5gpqfxvz6pve8xhufo1bcf77hqotyv5x.png)
Explanation:
Given y varies directly with x then the equation relating them is
y = kx ← k is the constant of variation
To find k use the condition y = 10 when x = - 3, thus
k =
=
= -
![(10)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5s5gpqfxvz6pve8xhufo1bcf77hqotyv5x.png)
y = -
x ← equation of variation
When x = - 1, then
y = -
× - 1 =
![(10)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5s5gpqfxvz6pve8xhufo1bcf77hqotyv5x.png)